1985
DOI: 10.1136/adc.60.12.1186
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic gastroenteritis.

Abstract: sis. The dramatic variation in values of creatine kinase activities in case 2 was unexplained. It was not obviously related to varying degrees of exertion before testing. This phenomenon has been described previously and could lead to diagnostic confusion. The condition is generally regarded as inherited on an autosomal recessive basis, but there is evidence to suggest genetic heterogeneity.These three patients' symptoms, dating from much earlier in childhood, confirm that type V glycogen storage disease may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In 19 cases, although multiple biopsies were performed, their results revealed normal mucosa. Because of negative biopsy results in the absence of pathological features at abdominal echo, CT scans or endoscopy, in 6 subjects [17][18][50][51][52][53] laparoscopy with peritoneal biopsies provided valuable information to achieve a definite diagnosis. In 3 patients surgery was not performed, and the diagnosis was established according to clinical and biological criteria [33,[54][55].…”
Section: Eosinophilic Gastroenteritis (Ege)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 19 cases, although multiple biopsies were performed, their results revealed normal mucosa. Because of negative biopsy results in the absence of pathological features at abdominal echo, CT scans or endoscopy, in 6 subjects [17][18][50][51][52][53] laparoscopy with peritoneal biopsies provided valuable information to achieve a definite diagnosis. In 3 patients surgery was not performed, and the diagnosis was established according to clinical and biological criteria [33,[54][55].…”
Section: Eosinophilic Gastroenteritis (Ege)mentioning
confidence: 99%
“…Surgery [27,37], ketotifen [82], azathioprine [16], sodium chromoglycate and montelukast [7,66] as monotherapy or in combination with corticosteroids were successfully used while treating relapses. Six patients required long-term steroid therapy [29,40,53,[83][84][85].…”
Section: Eosinophilic Gastroenteritis (Ege)mentioning
confidence: 99%
“…Firstly it has been suggested that it represents an allergic gastrointestinal response to a variety of allergens -a concept supported by a family and personal history of allergic disorders such as asthma, hayfever and hypersensitivity to drugs in 50-70% of patients (7 ,8). Several cases have been described where gastrointestinal symptoms have been exacerbated by a specific food challenge and responded to elimination diets (1,9). The concept of food allergy is by no means universally accepted however.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with EoN have elevated peripheral blood eosinophil counts, and even total white blood cell counts (43,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). In EoC, peripheral eosinophilia may occur in a proportion of patients (13,20), as well as iron deficiency anemia and hypoalbuminemia (20).…”
Section: Statement 6 the Available Data Do Not Allow Conclusion To Be...mentioning
confidence: 99%